Are the capital structures of JSE listed companies influenced by equity market timing? - Mpeke, Siyanda (College of Accounting, 2025)
Purpose Empirical research on capital structure in the South African context has primarily been focused on testing the speed of adjustment theory, pecking order theory and the trade-off theory. This dissertation sets out to test whether evidence of the market timing theory exists in JSE listed firms by applying the method used by De Bie and De Haan (2007) for evidence of market timing in Dutch firms; the regression model used to test market timing was developed by Baker and Wurgler (2002). Baker and Wurgler (2002) hypothesized that a firm's current capital structure is the cumulative result of past attempts to issue equity when share prices are high and repurchase equity when share prices are low; this is the market timing theory of capital structure. Design/methodology The method is applied to non-financial firms for the ten-year period including financial periods from 2012 to 2022. Specifically addressing the following question, is the current capital structure of JSE firms the cumulative result of past equity timing attempts? To test this hypothesis, the regression model which includes the externalfinance-weighted average market-to-book ratio (EFWAMB) variable will be used alongside the four common variables for capital structure, namely: firm size, tangibility, profitability, and market-to-book ratio (Allini et al., 2018; Baker & Wurgler, 2002; De Bie & De Haan, 2007; Hovakimian, 2006). The study applies a two-step system generalised method of moments (GMM). For robustness, a Generalized Least Square regression (GLS) was also conducted for robustness as well as descriptive statistics and the discussion of the results thereof. Findings The results show evidence for both the pecking order theory and trade-off theory. More importantly, the findings of this dissertation show evidence supporting the market timing theory of capital structure. Originality/value The market timing theory has become popular and has been tested in other markets (Hovakimian et al., 2004), however it has not been explicitly tested in South African firms. Adding the South African context further contributes to the capital structure literature and further tests the robustness of the theory or can help in identifying the circumstances in which the results of the study may differ